Highly efficient pure-blue organic light-emitting diodes based on rationally designed heterocyclic phenophosphazinine-containing emitters - Xing, Longjiang; Wang, Jianghui; Chen, Wen-Cheng; Liu, Bo; Chen, Guowei; Wang, Xiaofeng; Tan, Ji-Hua; Chen, Season Si; Chen, Jia-Xiong; Ji, Shaomin; Zhao, Zujin; Tang, Man-Chung; et al. (Nature communications, 2024)
Multi-resonance thermally activated delayed fluorophores have been actively studied for high-resolution photonic applications due to their exceptional color purity. However, these compounds encounter challenges associated with the inefficient spin-flip process, compromising device performance. Herein, we report two pure-blue emitters based on an organoboron multi-resonance core, incorporating a conformationally flexible donor, 10-phenyl-5 H -phenophosphazinine 10-oxide (or sulfide). This design concept selectively modifies the orbital type of high-lying excited states to a charge transfer configuration while simultaneously providing the necessary conformational freedom to enhance the density of excited states without sacrificing color purity. We show that the different embedded phosphorus motifs (phosphine oxide/sulfide) of the donor can finely tune the electronic structure and conformational freedom, resulting in an accelerated spin-flip process through intense spin-vibronic coupling, achieving over a 20-fold increase in the reverse intersystem crossing rate compared to the parent multi-resonance emitter. Utilizing these emitters, we achieve high-performance pure-blue organic light-emitting diodes, showcasing a top-tier external quantum efficiency of 37.6% with reduced efficiency roll-offs. This proposed strategy not only challenges the conventional notion that flexible electron-donors are undesirable for constructing narrowband emitters but also offer a pathway for designing efficient narrow-spectrum blue organic light-emitting diodes. The inefficient spin-flip process of multi-resonance emitters could compromise the device performance of light-emitting diodes. Here, the authors incorporate conformationally flexible donor to enhance the density of excited states, achieving 20-fold increase in reverse intersystem crossing rate.